EFISIENSI USAHATANI PADI SAWAH MELALUI PENGELOLAAN TANAMAN TERPADU DI KABUPATEN SERANG PROVINSI BANTEN - Haryani, Dewi (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2010)
The research was aimed at analyzing the technical efficiency, allocative and economic factors and the factorsthat influence the level of technical efficiency in lowland rice farming in Carenang district, Serang Regency, Bantenprovince. The analysis tool used was the method of Maximum Likelihood Estimation (MLE) due to the capabilityto explain the technical efficiency obtained by farmers as well as the factors affecting inefficiency. Allocativeefficiency and economic efficiency gained from the reduction of production cost of dual function. The number ofrespondent used consists of 120 farmes, 60 farmers of ICM program and 60 farmers are not from the ICM program.The results showed that the farmers of ICM program were more technically efficient (87%) than the farmers fromoutside of ICM program (71%). The technical efficiency of farmers in ICM program was affected by age,education, and planting systems, while the technical efficiency of farmers from non ICM program were influencedby education, the ratio of employment and unemployment persons, the participation in farmersâ groups and plantingsystems. The results of the analysis also showed that the allocative and economic farmers of ICM program weremore efficient than the farmers are non ICM program with 70.2 percent and 61 percent, respectively, for allocativeefficiency and economic efficiency and farmers are non ICM program, with 64.8% and 56.2%, respectively.Key words : ICM ,stochastic frontier,efficiency.Penelitian bertujuan menganalisis efisiensi teknis, alokatif dan ekonomis serta faktor faktor yangmempengaruhi tingkat efisiensi teknis pada usahatani padi sawah di Kecamatan Carenang, Kabupaten Serang,Provinsi Banten tahun 2008. Alat analisis yang digunakan adalah metode Maximum Likelihood Estimation(MLE). Jumlah responden 120 orang, terdiri dari 60 petani program Pengelolaan Tanaman Terpadu (PTT) dan 60 petani non program. Hasil penelitian menunjukkan bahwa petani program PTT lebih efisien secara teknisdibandingkan dengan petani non program dengan rata-rata tingkat efisiensi 87%, sedangkan petani non programhanya 71%. Efisiensi teknis petani program PTT dipengaruhi oleh umur, pendidikan dan sistem tanam sedangkanpetani non program efisiensi teknisnya dipengaruhi oleh pendidikan, ratio yang tidak bekerja dengan yangbekerja, partisipasi dalam kelompok tani dan sistem tanam. Hasil analisis juga menunjukan bahwa secara alokatifdan ekonomi petani program PTT lebih efisien dibandingkan dengan petani non program yaitu masing-masing70,2% dan 61% untuk petani program PTT, sedangkan petani non program masing-masing 64,8% dan 56,2%.Kata kunci : PTT, efisiensi teknis, efisiensi ekonomis